Kinetic of α-amylase inhibition by Gracilaria corticata and Sargassum angustifolium extracts and zinc oxide nanoparticles. (January 2020) - Nasab, Soudeh Bahramian; Homaei, Ahmad; Karami, Leila
Abstract: In this research, Gracilaria corticata red algae and Sargassum angustifolium brown algae were collected from tidal zones of the coastal areas of Bushehr (Persian Gulf coastline), and were extracted with methanol, ethanol, and sodium phosphate buffer. Zinc oxide nanoparticles were synthesized by chemical deposition. α-Amylase inhibition was evaluated using a colorimetric method based on the reduction of maltose released from a starch solution. The results showed that with increased sample concentration, the α-amylase was increasingly inhibited. The phosphate buffer extract of Gracilaria corticata showed the highest α-amylase inhibition, with an IC50 of 0.44 mg/mL and with inhibition following a competitive mechanism. The phosphate buffer extract of Sargassum angustifolium showed the lowest α-amylase inhibition with an IC50 of 1.85 mg/mL. Zinc oxide nanoparticles inhibited with an IC50 of 0.34 mg/mL with inhibition following a competitive mechanism. The two species of algae studied in this research, which both exhibited anti-diabetic activity, have potential for lowering intestinal glucose uptake in diabetic patients. Graphical abstract: Image 1 Highlights: α-amylase inhibition activity of Gracilaria corticata and Sargassum angustifolium. Zinc oxide nanoparticles can be considered as novel anti-diabetic drug supplements. Mechanism of α-amylase inhibition by kinetic studies.